The Didascalia Apostolorum: An English Version with Introduction and Annotation. By Alistair Stewart-Sykes - Doerfler, Maria E. (The journal of theological studies, 2010)
Late ancient church order literature has enjoyed a cautious revival of scholarly interest in recent years—a trend that has been encouraged by the availability of user-friendly editions and translations of the texts in question. Alistair Stewart-Sykes’s annotated English version of the Didascalia Apostolorum (DA) is the most recent contribution to this phenomenon. The explicit aim of Stewart-Sykes’s project is not the creation of a translation akin to that published by Vööbus in 1979, which seeks to stick as closely as possible to the Syriac manuscripts. Instead, like R. Hugh Connolly before him, Stewart-Sykes aims to provide a translation ‘for those whose primary interest is not in philology but in ecclesiastical history, liturgy, and/or early Judaism’ (p. 90).